Remaining fatigue life assessment of aging fixed steel offshore jacket platforms. Issue 2 (1st February 2016) - Zeinoddini, Mostafa; Ranjbar, Pooya; Khalili, Hadi; Ranaei, Alireza; Golpour, Hamid; Fakheri, Javad
Abstract : Actual fatigue life of an existing offshore platform typically deviates from that intended by its designer because aging platforms commonly experience some degradations, mechanical damages, repairs and modifications, and come across demands for the service extension. The current multidisciplinary paper focuses on different aspects of the remaining fatigue life assessment of an aging offshore platform. In the course of a case study, it describes a hindcasting technique for quantitative estimation of the long-term wave climatology, methods for geotechnical/structural modelling of the platform foundation to evaluate the piles fatigue damages accumulated during their driving and in-place service and the outlines for a spectral fatigue modelling and analysis of the fatigue damages to welded structural joints. Potential limitations in the available codes of practice, regarding the fatigue life assessment of existing offshore structures, are highlighted. The reliability of the fatigue life evaluations, possible remedy measures and some fatigue integrity monitoring techniques are discussed.